Qodariyah Wa Naqsabandiyah Tarekat Transformation Towards Social Piety - Nur fadilah; S.Fathiyatul Jannah; Faridatul Jannah (Penerbit Hellow Pustaka, 2024)
The aim of this research is to find out how the Qodariyah Wa Naqsabandiyah Order aims to determine the transformation of social piety. This research method is qualitative with the Pustaka (library research) research type. The results of this research are to determine qodariyah wa naqsabandiyah in its transformation towards social piety which in it describes the transformational forms of social piety, the transformation of the social and religious values of qodariyah adherents